2018
DOI: 10.1038/s41588-018-0128-6
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of subclonal selection in cancer from bulk sequencing data

Abstract: Subclonal architectures are prevalent across cancer types. However, the temporal evolutionary dynamics that produce tumor subclones remain unknown. Here we measure clone dynamics in human cancers by using computational modeling of subclonal selection and theoretical population genetics applied to high-throughput sequencing data. Our method determined the detectable subclonal architecture of tumor samples and simultaneously measured the selective advantage and time of appearance of each subclone. We demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
239
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(261 citation statements)
references
References 58 publications
21
239
1
Order By: Relevance
“…For instance, in P6, we identified 3 prominent mutation clusters; all 3 were present in all regions in the tumor, but at varying proportions ( Figure 1D). In addition, we adopted an orthogonal approach, and applied the method proposed by Williams et al (Williams et al, 2018) to assess clonal architecture and compare that with our estimates. Overall, the clonal architecture the tumors are similar to that inferred by PyClone, with 1-2 subclones per sample (Supplementary Figure 10).…”
Section: Patterns Of Genetic Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in P6, we identified 3 prominent mutation clusters; all 3 were present in all regions in the tumor, but at varying proportions ( Figure 1D). In addition, we adopted an orthogonal approach, and applied the method proposed by Williams et al (Williams et al, 2018) to assess clonal architecture and compare that with our estimates. Overall, the clonal architecture the tumors are similar to that inferred by PyClone, with 1-2 subclones per sample (Supplementary Figure 10).…”
Section: Patterns Of Genetic Heterogeneitymentioning
confidence: 99%
“…We also used a Bayesian approach developed by Williams et al (Williams et al, 2018), as implemented in their SubClonalSelection.jl to draw clonal inferences from variant allele frequencies. Subclonal architecture of each sample was detected and the selective advantage (s) and time of appearance of each subclone (t) were measured simultaneously, as recommended by the authors.…”
Section: Identification Of Subclones and Evolutionary Dynamics Paramementioning
confidence: 99%
“…S1). As several advanced studies have shown, [7][8][9]13,16,17 the proposed method also shows the advantage of using VAF information (mutation read counts and depths) rather than using only the presence or absence of mutations, to infer the tumor evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we considered the case that one positively selective subclone in the primary tumor appears in the WES samples. 13 One starting primary tumor cell with b = 1, d = 0.1 are assumed to evolve and at the time when the population reaches a particular population size, N sub. occ.…”
Section: Robustness For Cell Death and Selection In The Primary Tumormentioning
confidence: 99%
“…Fitness landscape-based methods could be used to measure how cancer cells adapt to treatments in vitro and there has been some success in measuring patient specific subclonal selection coefficients 43 .…”
Section: Discussionmentioning
confidence: 99%